UJARAN KEBENCIAN WARGANET PADA AKUN INSTAGRAM @UK (UKI KAUTSAR): KAJIAN LINGUISTIK FORENSIK - Vicno Triwira Dhika JR (Universitas Negeri Makassar, 2023)
Netizens Hate Speech on Instagram Account @UK (Uki Kautsar): Forensic Linguistics Study. This study aims to analyze hate speech contained in netizen comments on posts on the @UK Instagram account. This study uses a descriptive qualitative approach. The research data is hate speech in the form of comments by netizens on posts on the @UK Instagram account. The data source for this research is comments from netizens on posts on the @UK Instagram account. The data obtained and analyzed descriptively. Based on the results of data analysis, researchers found hate speech in the form of igniting and appeasing. Hate speech in the form of provocative actions is included in Article 160 of the Criminal Code. Hate speech in the form of hurtful acts can be subject to Article 315 of the Criminal Code. Hate speech is classified as hate speech in the form of abnormalities or disorders.